Comparative Genomics Analysis of Streptococcus tigurinus Strains Identifies Genetic Elements Specifically and Uniquely Present in Highly Virulent Strains. - Seydina M Diene (PLoS ONE, 2016)
Streptococcus tigurinus is responsible for severe invasive infections such as infective endocarditis, spondylodiscitis and meningitis. As described, S. tigurinus isolates AZ_3aT and AZ_14 were highly virulent (HV phenotype) in an experimental model of infective endocarditis and showed enhanced adherence and invasion of human endothelial cells when compared to low virulent S. tigurinus isolate AZ_8 (LV phenotype). Here, we sought whether genetic determinants could explain the higher virulence of AZ_3aT and AZ_14 isolates. Several genetic determinants specific to the HV strains were identified through extensive comparative genomics amongst which some were thought to be highly relevant for the observed HV phenotype. These included i) an iron uptake and metabolism operon, ii) an ascorbate assimilation operon, iii) a newly acquired PI-2-like pilus islets described for the first time in S. tigurinus, iv) a hyaluronate metabolism operon, v) an Entner-Doudoroff pathway of carbohydrates metabolism, and vi) an alternate pathways for indole biosynthesis. We believe that the identified genomic features could largely explain the phenotype of high infectivity of the two HV S. tigurinus strains. Indeed, these features include determinants that could be involved at different stages of the disease such as survival of S. tigurinus in blood (iron uptake and ascorbate metabolism operons), initial attachment of bacterial pathogen to the damaged cardiac tissue and/or vegetation that formed on site (PI-2-like pilus islets), tissue invasion (hyaluronate operon and Entner-Doudoroff pathway) and regulation of pathogenicity (indole biosynthesis pathway).